Yield response of diallelic crossed maize (Zea mays L.) genotypes to varying nitrogen regimes in Nigeria - Bello, OB; Afolabi, MS; Ige, SA; Abdulmaliq, SY; Azeez, MA; Mahmud, J (Journal of Bio-Science, 2012)
Context: Development of early maturing maize cultivars that remain productive under low N fertilizer farming system, consistent with the farmers technologies is a prerequisite to improving adoption of new varieties without increasing production cost. Objective: To assess the performance of ten early open pollination maize varieties (OPVs) and their F1 hybrids for grain yield and nitrogen use efficiency (NUE), and also identify productive cultivars under low N fertilizer regimes. Materials and Methods: The trials were set up in a split plot arrangement with three N fertilizer levels (0, 45 and 90 kg N ha-1) as main plot and the genotypes as sub-plot. Each plot within N level was four-row, laid out in a randomized complete block design of four replications. Ten OPVs were crossed in a half diallel to generate 45 F1 hybrids during 2004 and 2005 growing seasons. Planting were carried out on 20th July, 2005 and 2nd July, 2006. Agronomic characters studied were grain yield, maize establishment count, days to 50% tasselling and silking as well as plant and ear heights. Results: The year 2005 growing season was better for all observed characters amongst all the genotypes than the year 2006. Although, expressions of these traits in the hybrids were relatively higher than the OPVs including the grain yield. The total increase in grain yield observed was 1.72 t ha-1 and 1.95 t ha-1 for OPVs and hybrids respectively on application of 90 kg ha-1 over no N-application. However, NUE was optimum at 45 kg N ha-1 in both groups. Grain yield and NUE correlated positively with growth characters measured except for days to 50% silking. Higher genetic gains were recorded for plant and ear heights. Conclusion: Two drought tolerant varieties (Acr 90 Pool 16-Dt and Tze Comp3 Dt) that combined well with specific cultivars for grain yield and NUE probably have gene pools for low N-tolerance. DOI: http://dx.doi.org/10.3329/jbs.v19i0.13000 J. bio-sci. 19 43-52, 2011